Urgency and necessity of Epstein-Barr virus prophylactic vaccines - Zhong, Ling; Krummenacher, Claude; Zhang, Wanlin; Hong, Junping; Feng, Qisheng; Chen, Yixin; Zhao, Qinjian; Zeng, Mu-Sheng; Zeng, Yi-Xin; Xu, Miao; Zhang, Xiao (npj vaccines, 2022)
Epstein-Barr virus (EBV), a γ-herpesvirus, is the first identified oncogenic virus, which establishes permanent infection in humans. EBV causes infectious mononucleosis and is also tightly linked to many malignant diseases. Various vaccine formulations underwent testing in different animals or in humans. However, none of them was able to prevent EBV infection and no vaccine has been approved to date. Current efforts focus on antigen selection, combination, and design to improve the efficacy of vaccines. EBV glycoproteins such as gH/gL, gp42, and gB show excellent immunogenicity in preclinical studies compared to the previously favored gp350 antigen. Combinations of multiple EBV proteins in various vaccine designs become more attractive approaches considering the complex life cycle and complicated infection mechanisms of EBV. Besides, rationally designed vaccines such as virus-like particles (VLPs) and protein scaffold-based vaccines elicited more potent immune responses than soluble antigens. In addition, humanized mice, rabbits, as well as nonhuman primates that can be infected by EBV significantly aid vaccine development. Innovative vaccine design approaches, including polymer-based nanoparticles, the development of effective adjuvants, and antibody-guided vaccine design, will further enhance the immunogenicity of vaccine candidates. In this review, we will summarize (i) the disease burden caused by EBV and the necessity of developing an EBV vaccine; (ii) previous EBV vaccine studies and available animal models; (iii) future trends of EBV vaccines, including activation of cellular immune responses, novel immunogen design, heterologous prime-boost approach, induction of mucosal immunity, application of nanoparticle delivery system, and modern adjuvant development.